Forkhead box protein 1 transcriptionally activates sestrin1 to alleviate oxidized low-density lipoprotein-induced inflammation and lipid accumulation in macrophages. Issue 2 (1st February 2022) - Gao, Feng; Zhao, Yongcheng; Zhang, Bin; Xiao, Chunwei; Sun, Zhanfa; Gao, Yuan; Dou, Xueyong
ABSTRACT: Transcription factor forkhead box protein 1 (FOXP1) has been shown cardiovascular protection. We aimed to analyze the role of FOXP1 in oxidized low-density lipoprotein (ox-LDL)-induced macrophages and its possible regulatory effect on sestrin1 (SESN1) expression. After stimulation with ox-LDL, FOXP1 expression in RAW264.7 cells was evaluated with RT-qPCR and Western blotting. Then, FOXP1 was overexpressed, followed by detection of inflammatory mediator levels using ELISA kits and RT-qPCR. Lipid accumulation was detected with oil red O staining. Additionally, the JASPAR database was used to predict the potential genes that could be transcriptionally regulated by FOXP1. ChIP and luciferase reporter assays were used to verify this combination. To further clarify the regulatory effects of FOXP1 on SESN1 in damage of macrophages triggered by ox-LDL, SESN1 was silenced to determine the inflammation and lipid accumulation under the condition of FOXP1 overexpression. Results indicated that ox-LDL stimulation led to a significant decrease in FOXP1 expression. FOXP1 overexpression notably reduced the levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, accompanied by a decreased in phosphorylated NF-κB p65 expression. Besides, FOXP1-upregulation inhibited lipid accumulation and reduced CD36 expression level in RAW264.7 cells upon ox-LDL stimulation. Moreover, results of ChIP and luciferase reporter assays suggested that FOXP1 could transcriptionally regulate SESN1 expression. Further experiments supported that SESN1 silencing restored the inhibitory effects of FOXP1 overexpression on the inflammation and lipid accumulation in RAW264.7 cells exposed to ox-LDL. Collectively, FOXP1 transcriptionally activates SESN1 for the alleviation of ox-LDL-induced inflammation and lipid accumulation in macrophages.